The report on sustainable development and investments in the agricultural sector: the environmental capital perspective - Metelytsia, Volodymyr Mykhailovych; Kolisnyk, Olena Pylypivna; Gagalyuk, Taras Vasylovych (Державний університет “Одеська політехніка”, 2024)
Ukrainian agribusiness works in challenging conditions today, and the international community greatly supports it. The decision to grant Ukraine the status of acandidate for EU accession, adopted by the European Coun-cil in June 2022, and initiatives such as the provision of financial assistance under the Ukraine Facility program (June 2023) opened up new opportunities for the agricultural sector of Ukraine. The realization of these opportunities depends not only on Ukraine’sability to carry out reforms in the direction of European integration but also on the readiness of business entities to overcome the consequences of hostilities through recovery and reconstruction. Purpose. The article aims to provide scientific jus-tification for the standardized forms of the Report on Sustainable Development and Investments (ESGI-report) in the agricultural sector of the economy for the preparation and publication of environmental capital indicators. Methods. The methods of induc-tion and deduction, analysis, and synthesis formed the basis for developing environmental indicators for the ESGI report. The abstract-logical method became the basis for the study of the norms of European legislation and the leading systems for meas-uring sustainable development. The analogy method made it possible to propose indicative (reference) indicators for measuring sustainable development at the micro level. Results. The article systematizes the estimated and verifiable indicators of ecological capital. The first group includes risks and opportunities connected with climate change, the transition to sustainable technolo-gies, and martial law. The second group comprises indicators that can be accurately measured with the help of calculators and technical means. They are related to the use of natural resources and the impact on the environment. To prepare the ESGI report, it is proposed that all materials posted on the Sustainable Reporting Platform (SR platform) be used: reporting forms, survey questionnaires, video recordings, as well as materials of webinars, presentations, and articles. The SR platform was developed within the framework of the MSCA4Ukraine program funded by the European Union. Conclusion. Attracting foreign investments for the post-war reconstruction of Ukraine’sagribusiness is impossible without preparing and disclosing non-financial informa tion about environmental capital at the micro level. One of the tools for disclosing such information is the ESGI report, which is posted on the SR platform. It is advisable to publish environmental indicators in standardized reporting forms to ensure their comparability with the data of other enterprises. At the same time, to assess the level of sustainable development, it is necessary to apply scientifically based reference values, which are based on best practices, statistical data and the company’s own experience.

Сьогодні український агробізнес працює в надскладних умовах, а міжнародна спільнота докладає неабияких зусиль для його підтримки. Рішення про надання Україні статусу кандидата на вступ до ЄС, прийняте Європейською радою у червні 2022 року, та такі ініціативи, як надання фінансової допомоги за програмою Ukraine Facility (червень 2023 року), відкрило нові можливості для аграрного сектору України. Реалізація цих можливостей залежить не тільки від здатності України провести реформи у напрямку євроінтеграції, але і від готовності суб’єктів господарювання подолати наслідки бойових дій шляхом реконструкції та відбудови. Метою статті є наукове обґрунтування стандартизованих форм Звіту зі сталого розвитку та інвестицій в аграрному секторі економіки – ESGI-звіту (Report on Sustainable Development and Investments) для підготовки і оприлюднення показників екологічного капіталу. За допомогою методів індукції та дедукції, аналізу та синтезу розроблено екологічні показники ESGI-звіту. Використання методу аналогії дозволило запропонувати орієнтирні (референтні) показники для вимірювання сталого розвитку на мікрорівні. Абстрактно-логічний метод ліг в основу вивчення норм європейського законодавства та провідних систем вимірювання сталого розвитку. У статті систематизовано оціночні та підтверджувані показники екологічного капіталу. До першої групи віднесено ризики та можливості: кліматичні; пов’язані з переходом на сталі технології; пов’язані з воєнним станом. Друга група – це показники, які можна точно виміряти за допомогою калькуляторів, технічних засобів. Вони пов’язані з використанням природних ресурсів і впливом на навколишнє середовище. Для підготовки ESGI-звіту запропоновано використовувати всі матеріали, розміщені на Платформі звітності сталого розвитку (Sustainable Reporting Platform, – SR-платформа): форми звітності, анкети опитування, відеозаписи і матеріали вебінарів, презентації, статті. Розробка SR-платформи здійснена в рамках програми MSCA4Ukraine, яка фінансується Європейським Союзом. Залучення іноземних інвестицій для післявоєнної відбудови агробізнесу України неможливе без підготовки і оприлюднення нефінансової інформації про екологічний капітал на мікрорівні. Одним із інструментів розкриття такої інформації є розроблений нами ESGI-звіт, який розміщений на SR-платформі. Оприлюднення екологічних показників доцільно здійснювати в стандартизованих звітних формах для забезпечення їх порівнюваності з даними інших підприємств. При цьому для оцінки рівня сталого розвитку необхідно застосовувати науково-обґрунтовані орієнтирні значення, які базуються на кращій практиці, статистичних даних та власному досвіді підприємства.
Keywords: climate-smart technologies; precision and organic farming; low-carbon and energy-saving technologies; ESGI report; post-war reconstruction of Ukrainian agribusiness; кліматично-розумні технології; точне і органічне землеробство; низьковуглецеві і енергозберігаючі технології; ESGI-звіт; післявоєнна реконструкція агробізнесу України